Kiai and Adherents Relations in the Contemporary Commodification - Aziz, Moh. Ali (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Kiai is an agent of change for the Islamic community in the land of Java, Indonesia. The status of kiai is pinned as a form of respect for his charismatic leadership for his adherents. The relation between the kiai and his adherents in the context of contemporary Islamic preaching (da'wa) can be studied through social exchange theory. This theory is relevant to da'wa activities involving the relationship between preachers and da'wa partners. Preachers involve attributes and statuses that are well packaged, so that da'wa partners get satisfaction. da'wa partners sacrifice times, properties, and energies to participate in da'wa activities. When modernization breaks through da'wa activities, preachers need an intermediary called a commodification agent of religion. Finally, da'wa activity is determined by the commodification agent, not the kiai as a preacher. The exchange of kiai with adherents involves the commodification of religious agents in two ways; attribute and status. Status is in the form of the role of kiai, which includes knowledge, example, and dedication. All exchange materials are processed by the commodification agent through media means; institutions, teaching assemblies, and houses of worship. Commodification agents can take the forms of committees, management of institutions, media managers, event organizers, or kiai assistants. The exchange of kiai produced a message of preaching, whether in the form of sound, images, or both sound and images.